The essential guide to Western civilization - Waddy, Nicholas J., author. aut Link Link Link
1 online resource
Keywords: "This new edition of The Essential Guide to Western Civilization provides a succinct and engaging overview of European history for students. With wide chronological coverage, from early humans and the first civilizations to the present, this book provides a narrative of key events in the West with insightful analysis to further contextualize the relationship of the West to the wider world. The second edition has been fully updated, with increased coverage of women, slavery, colonization, economics and finance, and concurrent developments in the non-Western world. It engages with recent scholarship and includes updated suggested readings to offer a more comprehensive view of Western civilization. To further aid student understanding, the book includes review questions at the end of each section, key terms and definitions for each chapter, discussion questions at the end of every chapter, and maps and images to illustrate important concepts. Ideal for undergraduates in Western Civilization and European history courses, this volume is a concise, accessible resource that encourages students to think critically and creatively about history"-- Provided by publisher.